STUDI GAMBAR ILUSTRASI PADA KORAN PADANG EKSPRES - RAFLES CANDRA RAMBEY, Drs. Syafwan, M.Si., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2016)
This research is to describe the kind, technical, and Function of Illustration Picture on Padang Ekspres. The method uded is a qualitative researcg with descriptive approach. The type of data that used are primary data and secondary data with the sources of primary data obtained from visual data on photo illustration padang Ekspres News Paper, while the secondary data obtained from direct narrative informant, the illustration and chief editor of Padang Ekspres. The results of the study found that the type of illustration used in the Padang Express Newspaper is Caricature, Cartoon, and Vector. Paper-making techniques in Padang Express Newspaper is using a mix of manual and computer techniques. The function of an illustration in the Padang Express Newspaper is to clarify the meaning of the story as well as a discourse also the attractiveness and beauty of its own in the newspaper.Kata kunci: Studi, Gambar, Ilustrasi, Jenis, Teknik, Fungsi, Padang Ekspres